Post-Covid Renal Mucormycosis: A Case Report - B. Madhumitha; Ganesh Rajagopal; N. Karunakaran; T. Mukuntharajan (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
The Pandora's box has been opened in the twenty-first century unleashing "the Coronavirus." There has been an increase in the incidence of mucormycosis during this coronavirus disease 2019 (COVID-19) pandemic with many case reports of rhino-orbito-cerebral and pulmonary mucormycosis. Diabetes mellitus, COVID, and Mucor fungus together are a dangerous trio associated with high mortality. We report a rare case of renal mucormycosis following COVID pneumonia in a 64-year-old patient with uncontrolled diabetes; with the imaging findings of left emphysematous pyelonephritis and cystitis, nonfunctioning left kidney, and left main renal artery and vein thrombosis. This is the first such case reported to our knowledge. A high degree of clinical suspicion with prompt recognition of imaging findings is essential to improve the chances of survival in such patients.